Comprehensive Comparison of Effects of Antioxidant (Astaxanthin) Supplementation from Different Sources in Haliotis discus hannai Diet - Weiguang Zou; Jiawei Hong; Wenchao Yu; Yaobin Ma; Jiacheng Gan; Yanbo Liu; Xuan Luo; Weiwei You; Caihuan Ke (MDPI AG, 2023)
Dietary antioxidant supplementation, especially astaxanthin, has shown great results on reproductive aspects, egg quality, growth, survival, immunity, stress tolerance, and disease resistance in aquatic animals. However, the effects of dietary astaxanthin supplementation from different sources are still unknown. A comprehensive comparison of survival, growth, immune response, antioxidant activity, thermal resistance, disease resistance, and intestinal microbial structure was conducted in dietary antioxidant supplementation from the sources of Gracilaria lemaneiformis (GL), industrial synthetic astaxanthin (80 mg/kg astaxanthin actual weight, named as group 'SA80'), Phaffia rhodozyma (80 mg/kg astaxanthin actual weight, named as group 'PR80') and Haematococcus pluvialis (120 mg/kg astaxanthin actual weight, named as group 'HP120') at their optimal supplementation amounts. Furthermore, the SA80, PR80, and HP120 groups performed better in all aspects, including survival, growth, immune response, antioxidant activity, thermal resistance, and disease resistance, compared with the GL group. The PR80 and HP120 group also had a better growth performance than the SA80 group. In terms of heat stress and bacterial challenge, abalone in the PR80 group showed the strongest resistance. Overall, 80 mg/kg astaxanthin supplementation from Phaffia rhodozyma was recommended to obtain a more effective and comprehensive outcome. This study contributes to the discovery of the optimum dietary astaxanthin supplementation source for abalone, which is helpful to improve the production efficiency and economic benefits of abalone. Future research can further explore the action mechanism and the method of application of astaxanthin to better exploit its antioxidant role.